2005
DOI: 10.1074/jbc.c500400200
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia-telangiectasia-mutated (ATM) Is a T-antigen Kinase That Controls SV40 Viral Replication in Vivo

Abstract: . Our findings uncover a direct link between ATM and SV40 LTag that may have implications for understanding the replication cycle of oncogenic polyoma viruses.The eukaryotic DNA damage response represents a series of highly integrated and tightly regulated pathways that coordinate DNA repair, cell cycle, and homeostatic responses to abnormal DNA structures arising endogenously or following exposure to extrinsic genotoxic stimuli. Central to the DNA damage response are a pair of structurally and functionally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
124
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(130 citation statements)
references
References 61 publications
6
124
0
Order By: Relevance
“…DDR kinases such as ATM may also phosphorylate baculovirus replicative factors to activate them for vDNA synthesis. This mechanism has been proposed for ATMdriven phosphorylation of simian virus 40 (SV40) large T-antigen, which is required for optimal SV40 replication (57). Indeed, we recently demonstrated that phosphorylation of the essential replicative factor IE1 of AcMNPV coincides with vDNA replication (62).…”
Section: Discussionmentioning
confidence: 99%
“…DDR kinases such as ATM may also phosphorylate baculovirus replicative factors to activate them for vDNA synthesis. This mechanism has been proposed for ATMdriven phosphorylation of simian virus 40 (SV40) large T-antigen, which is required for optimal SV40 replication (57). Indeed, we recently demonstrated that phosphorylation of the essential replicative factor IE1 of AcMNPV coincides with vDNA replication (62).…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the expression of the insulin growth factor receptor-I in normal fibroblasts and AT-mutated fibroblasts showed decreased levels of insulin growth factor-I receptor in ATmutated cells and identified Sp1 as a potential mediator between ATM and insulin growth factor-I receptor expression (38). In addition, ATM is induced by infection of cells with herpes simplex virus-1 and SV40 (71,72), which also induce Sp1 phosphorylation (11,20). Kim and DeLuca have shown that phosphorylated Sp1 purified from herpes simplex virus-1 -infected cells has decreased ability to activate transcription in in vitro transcription assays and that the kinetics of the phosphorylation correlate with the expression of Sp1-independent viral late genes, suggesting a viral-mediated temporal regulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Human Papillomavirus 16 E7 oncoprotein attenuates DNA damage checkpoint control by increasing the proteolytic turnover of claspin (75). SV40 large T antigen is a target of ATM kinase, and this ATM-mediated phosphorylation of T-antigen is required for optimal viral DNA synthesis (77). Inhibition of ATM activity decreases SV40 DNA replication and delays recruitment of T-antigen and DNA repair proteins to viral replication foci (76 -78).…”
Section: Discussionmentioning
confidence: 99%